Rubber composition
A rubber composition with unsaturated fatty acids and cobalt acetyl acetonato maintains adhesion and crack resistance in rubber goods, addressing the aging-related adhesiveness issue in existing compositions.
Patent Information
- Application Number
- JP2023516160
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-10
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2040-09-10
AI Technical Summary
Existing rubber compositions containing cobalt acetyl acetonato face a reduction in adhesiveness after aging, which affects the adhesive properties of rubber goods like tires.
A rubber composition comprising a mixture of unsaturated fatty acids, reinforced fillers, and cobalt acetyl acetonato, with specific proportions and processing methods, enhances adhesion and crack resistance over time.
The composition maintains or improves initial adhesion and crack resistance, ensuring better adhesive properties even after aging.
Smart Images

Figure 0007624508000001 
Figure 0007624508000002
Abstract
Description
[Technical field]
[0001] The field of the invention is in particular that of rubber compositions intended for rubber articles, more particularly for rubber composites or for tires. [Background technology]
[0002] The ability of a rubber composition to be tacky before curing is an important property for the manufacture of rubber articles. Indeed, to make rubber articles, in particular tires, it is necessary to be able to apply different layers of the rubber article to each other, and it is also necessary for these layers to stick to each other before curing the rubber article, which is done to crosslink the layers to each other. This tackiness property of the composition before curing (vulcanization) is also called "tackiness", "uncured tack", "unvulcanized tack" or "green tack". [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-325302 A
[0004] Patent Document 1 discloses a rubber composition containing cobalt acetylacetonate to provide excellent rupture characteristics.
[0005] However, the rubber composition disclosed in Patent Document 1 has a problem, and there is concern that the tackiness of the rubber composition, particularly the tackiness after aging, may be reduced by cobalt acetylacetonate. During research, the inventors discovered that certain rubber compositions, especially intended for rubber articles, can unexpectedly improve adhesion after aging while maintaining or improving initial adhesion and crack resistance.
[0006] In this specification, unless expressly indicated otherwise, all percentages (%) refer to weight percent (wt%). The expression "elastomeric matrix" is understood to mean, in a given composition, all the elastomers present in said rubber composition. The abbreviation "phr" stands for parts by weight per 100 parts by weight of elastomeric matrix in the rubber composition considered. In this specification, unless otherwise clearly indicated, each Tg DSC The (glass transition temperature) is measured in a known manner by DSC (differential scanning calorimetry) according to standard ASTM D3418-08. Any interval of values indicated by the expression "between a and b" refers to a range of values greater than "a" to less than "b" (i.e. excluding the endpoints a and b), whereas any interval of values indicated by the expression "a to b" refers to a range from value "a" to value "b" (i.e. including the precise endpoints a and b). The expression "based on" is to be understood in the present application to mean a composition comprising a mixture of the various components used, or the product of a reaction of the various components used, or both, some of which can or are intended to react with one another, at least in part, during the various stages of the preparation of said composition, in particular during vulcanization (curing). Summary of the Invention [Means for solving the problem]
[0007] A first aspect of the present invention is a rubber composition, preferably an adhesive rubber composition, based on an elastomeric matrix, a reinforcing filler, cobalt acetylacetonate and a fatty acid based on more than 10% by weight, preferably more than 20% by weight, more preferably more than 30% by weight, even more preferably more than 40% by weight of unsaturated fatty acids per 100% by weight of fatty acids. Effect of the Invention
[0008] The specific rubber composition makes it possible to unexpectedly improve adhesion after aging while maintaining or improving initial adhesion and crack resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Each of the following aspects, embodiments, examples, and variations, including each preferred range, each preferred item, or both, can be applied to any of the other aspects, other embodiments, other examples, and other variations of the present invention, unless otherwise expressly indicated. The rubber composition of the present invention is based on an elastomeric matrix. A "diene" type elastomer (or loosely "rubber", both terms being synonymous) is to be understood as being one or more elastomers (i.e., homopolymers or copolymers) derived at least in part from diene monomers (monomers having two conjugated or non-conjugated carbon-carbon double bonds), as is known. These diene elastomers can be divided into two categories: "essentially unsaturated" or "essentially saturated". In general, the expression "essentially unsaturated" is understood to mean diene elastomers that are derived at least in part from conjugated diene monomers with a content of units derived from dienes (conjugated dienes) of more than 15% (mol %). Diene elastomers such as butyl rubber or diene / α-olefin copolymers of the EPDM type are therefore not included in the above definition and can in particular be described as "essentially saturated" diene elastomers (having a low or very low content of units derived from dienes (always less than 15%)). Within the category of "essentially unsaturated" diene elastomers, the expression "highly unsaturated" diene elastomers is understood to mean in particular diene elastomers with a content of units derived from dienes (conjugated dienes) of more than 50%. Although applicable to any type of diene elastomer, those skilled in the art of tires will appreciate that essentially unsaturated diene elastomers are preferred for use in the present invention.
[0010] Given these definitions, the expression diene elastomers which may be used in the composition of the invention means in particular (a) any homopolymer obtained by polymerization of a conjugated diene monomer, preferably said homopolymer having from 4 to 12 carbon atoms; (b) is understood to mean any copolymer obtained by copolymerization of one or more conjugated dienes with one another or with one or more vinyl aromatic compounds, preferably having from 8 to 20 carbon atoms. The following are particularly suitable as conjugated dienes: 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-di(C1-C5 alkyl)-1,3-butadiene, such as 2,3-dimethyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2-methyl-3-ethyl-1,3-butadiene or 2-methyl-3-isopropyl-1,3-butadiene, aryl-1,3-butadienes, 1,3-pentadiene or 2,4-hexadiene, etc. The following are, for example, suitable as vinyl aromatic compounds: styrene, ortho-, meta- or para-methylstyrene, the commercial mixture of "vinyl toluene", para-(tert-butyl)styrene, methoxystyrene, chlorostyrene, vinyl mesitylene, divinylbenzene or vinyl naphthalene.
[0011] A second aspect of the present invention is the rubber composition according to the first aspect, wherein the elastomeric matrix comprises at least one diene elastomer selected from the group consisting of polyisoprene, polybutadiene, butadiene copolymers, isoprene copolymers, and combinations thereof. According to a preferred embodiment of the second aspect, the polybutadiene has a content (mol %) of 1,2-units between 4% and 80% or a content (mol %) of cis-1,4-units of more than 80% (mol %), more preferably more than 90% (mol %), even more preferably at least 96% (mol %). According to a preferred embodiment of the second aspect, the polyisoprene is natural rubber (NR), synthetic polyisoprene (IR) or a combination thereof. The synthetic polyisoprene may be synthetic cis-1,4-polyisoprene, preferably having a content (mol %) of cis-1,4 bonds of more than 90%, more preferably more than 95%, even more preferably more than 98%. According to a preferred embodiment of the second aspect, the butadiene copolymer is selected from the group consisting of styrene butadiene copolymer (SBR), butadiene isoprene copolymer (BIR), styrene butadiene isoprene copolymer (SBIR), and combinations thereof. According to a preferred embodiment of the second aspect, the isoprene copolymer is selected from the group consisting of butadiene isoprene copolymers (BIR), styrene isoprene copolymers (SIR), styrene butadiene isoprene copolymers (SBIR) and combinations thereof.
[0012] A third aspect of the present invention is the rubber composition according to the first or second aspect, wherein the elastomeric matrix comprises more than 50 phr, preferably more than 60 phr, more preferably more than 70 phr, even more preferably more than 80 phr, particularly more than 90 phr, more particularly more than 95 phr, and even more particularly 100 phr of polyisoprene. According to a preferred embodiment of the second or third aspect, the polyisoprene comprises more than 50% by weight, preferably more than 60% by weight, more preferably more than 70% by weight, even more preferably more than 80% by weight, particularly more than 90% by weight, more particularly more than 95% by weight, and even more particularly 100% by weight of natural rubber per 100% by weight of polyisoprene. The rubber composition of the present invention is based on a reinforcing filler. Any type of reinforcing filler known for its ability to reinforce rubber compositions that can be used to manufacture articles may be used, for example, a reinforcing organic filler (such as carbon black), a reinforcing inorganic filler (such as silica in combination with a coupling agent in a known manner), or a combination of a reinforcing organic filler and a reinforcing inorganic filler. Suitable carbon blacks are all carbon blacks conventionally used in tires ("tire-grade" blacks), such as reinforcing carbon blacks of the ASTM grades 100, 200 or 300 series (such as, for example, N115, N134, N234, N326, N330, N339, N347 or N375 blacks) or higher carbon black series such as the ASTM grades 500, 600, 700 or 800 series (such as, for example, N550, N660, N683, N772, N774 blacks). Carbon blacks may, for example, already be present in the elastomer matrix, for example in diene elastomers, in the form of masterbatches (see, for example, applications WO97 / 36724 or WO99 / 16600).
[0013] A fourth aspect of the present invention is the rubber composition according to any one of the first to third aspects, wherein the reinforcing filler comprises more than 50 mass %, preferably more than 60 mass %, more preferably more than 70 mass %, even more preferably more than 80 mass %, particularly more than 90 mass %, more particularly more than 95 mass %, and even more particularly 100 mass % of carbon black per 100 mass % of the reinforcing filler. A fifth aspect of the present invention is a rubber composition according to any one of the first to fourth aspects, wherein the content of the reinforcing filler is between 10 phr and 100 phr, preferably between 20 phr and 90 phr, more preferably between 30 phr and 80 phr, even more preferably between 40 phr and 70 phr, and in particular between 50 phr and 60 phr.
[0014] The rubber composition of the present invention is based on cobalt acetylacetonate. A sixth aspect of the present invention is the rubber composition according to any one of the first to fifth aspects, wherein the cobalt acetylacetonate is selected from the group consisting of cobalt(II) acetylacetonate, cobalt(III) acetylacetonate, and combinations thereof, and is preferably cobalt(II) acetylacetonate which is cobalt(II) 4-oxopent-2-en-2-oleate. A seventh aspect of the present invention is the rubber composition according to any one of the first to sixth aspects, wherein the content of cobalt acetylacetonate is between 0.1 phr and 2.0 phr, preferably between 0.5 phr and 1.5 phr. According to a preferred embodiment, the rubber composition does not contain cobalt salts other than cobalt acetylacetonate or is based on at least one cobalt salt other than cobalt acetylacetonate, the mass of the cobalt salt other than cobalt acetylacetonate being less than the mass of the cobalt acetylacetonate.
[0015] The rubber composition of the present invention is based on a fatty acid having more than 10% by weight of unsaturated fatty acids per 100% by weight of fatty acids. The fatty acids may further be based on saturated fatty acids, which are aliphatic monocarboxylic acids with no unsaturated bonds in the hydrocarbon chain, for example palmitic acid, stearic acid. Unsaturated fatty acids are aliphatic monocarboxylic acids that have at least one unsaturated bond in the hydrocarbon chain. An eighth aspect of the present invention is the rubber composition according to any one of the first to seventh aspects, wherein the content of the fatty acid is between 0.1 phr and 2.0 phr, preferably between 0.2 phr and 1.0 phr. A ninth aspect of the present invention is the rubber composition according to any one of the first to eighth aspects, in which the content of the unsaturated fatty acid per 100 mass% of the fatty acid is more than 50 mass%, preferably more than 60 mass%. According to a preferred embodiment of the invention, the content of unsaturated fatty acids per 100% by weight of fatty acids is at most 100% by weight.
[0016] A tenth aspect of the present invention is the rubber composition according to any one of the first to ninth aspects, wherein the unsaturated fatty acid is a straight-chain unsaturated fatty acid having 4 to 30 carbon atoms, preferably 8 to 26 carbon atoms, more preferably 12 to 22 carbon atoms, and even more preferably 16 to 18 carbon atoms. According to a preferred embodiment of the tenth aspect, the linear unsaturated fatty acid has at least 12 carbon atoms, and the first carbon-carbon double bond of the linear unsaturated fatty acid is located at the third carbon or more, preferably the fifth carbon or more, more particularly the sixth carbon or more, counting from the terminal methyl side of the linear unsaturated fatty acid. According to a preferred embodiment of the invention, the unsaturated fatty acids (IUPAC names) are butenoic acid (C4), pentenoic acid (C5), hexenoic acid (C6), heptenoic acid (C7), octenoic acid (C8), nonenoic acid (C9), decenoic acid (C10), undecenoic acid (C11), dodecenoic acid (C12), tridecenoic acid (C13), tetradecenoic acid (C14), pentadecenoic acid (C15), hexadecenoic acid (C16), heptadecenoic acid (C17), Based on at least one of octadecenoic acid (C18), nonadecenoic acid (C19), icosenoic acid (C20), henicosenoic acid (C21), docosenoic acid (C22), tricosenoic acid (C23), tetracosenoic acid (C24), pentacosenoic acid (C25), hexacosenoic acid (C26), heptacosenoic acid (C27), octacosenoic acid (C28), nonacosenoic acid (C29), tricosenoic acid (C30), or combinations thereof.
[0017] An eleventh aspect of the present invention is the rubber composition according to any one of the first to tenth aspects, wherein the unsaturated fatty acid has 1 to 6 carbon-carbon double bonds, preferably 1 to 5 carbon-carbon double bonds, more preferably 1 to 4 carbon-carbon double bonds, and even more preferably 1 to 3 carbon-carbon double bonds. A twelfth aspect of the present invention is a rubber composition according to any one of the first to eleventh aspects, in which the unsaturated fatty acid is based on more than 10 mass%, preferably more than 20 mass%, more preferably more than 30 mass%, even more preferably more than 40 mass%, and particularly preferably more than 50 mass% of polyunsaturated fatty acid per 100 mass% of unsaturated fatty acid. According to a preferred embodiment of the twelfth aspect, the polyunsaturated fatty acid has at least two carbon-carbon double bonds, preferably from 2 to 6 carbon-carbon double bonds, more preferably from 2 to 5 carbon-carbon double bonds, even more preferably from 2 to 4 carbon-carbon double bonds, and in particular from 2 to 3 carbon-carbon double bonds.
[0018] According to a preferred embodiment of the present invention, the unsaturated fatty acids (common names) are myristoleic acid (C14, monounsaturated fatty acid, n-5), palmitoleic acid (C16, monounsaturated fatty acid, n-7), stearidonic acid (C18, tetraunsaturated fatty acid, n-3), vaccenic acid (C18, monounsaturated fatty acid, n-7), oleic acid (C18, monounsaturated fatty acid, n-9), elaidic acid (C18, monounsaturated fatty acid, n-9), linoleic acid (C18, diunsaturated fatty acid, n-6), α-linolenic acid (C18, triunsaturated fatty acid, n-3), γ-linolenic acid (C18, triunsaturated fatty acid, n-4), α-linolenic acid (C18, triunsaturated fatty acid, n-5), α-linolenic acid (C18, triunsaturated fatty acid, n-6), α-linolenic acid (C18, triunsaturated fatty acid, n-7), α-linolenic acid (C18, triunsaturated fatty acid, n-8), α-linolenic acid (C18, triunsaturated fatty acid, n-9 ... unsaturated fatty acid, n-6), gadoleic acid (C20, monounsaturated fatty acid, n-11), eicosenoic acid (C20, monounsaturated fatty acid, n-11), eicosadienoic acid (C20, diunsaturated fatty acid, n-6), arachidonic acid (C20, tetraunsaturated fatty acid, n-6), eicosapentaenoic acid (C20, pentaunsaturated fatty acid, n-3), erucic acid (C22, monounsaturated fatty acid, n-9), docosahexaenoic acid (C22, hexausaturated fatty acid, n-3), nervonic acid (C24, monounsaturated fatty acid, n-9), or combinations thereof. Please note that the nx (x = 3, 5, 6, 7, 9, and 11) in parentheses after the compound name represents the carbon position of the first carbon-carbon double bond, counting from the methyl group side, which is the end of the unsaturated fatty acid.
[0019] A thirteenth aspect of the present invention is a rubber composition according to any one of the first to twelfth aspects, wherein the unsaturated fatty acid is based on at least one selected from the group consisting of oleic acid, linoleic acid, α-linolenic acid, and combinations thereof, and preferably the amount of linoleic acid is greater than the amount of oleic acid, more preferably the amount of linoleic acid is greater than the amount of α-linolenic acid, and even more preferably the amount of oleic acid is greater than the amount of α-linolenic acid. The rubber composition of the present invention may be based on all or at least a portion of the usual additives commonly used in rubber compositions for rubber articles, such as protective agents (antiozonant waxes, chemical antiozonants, antioxidants, etc.), plasticizers (e.g., liquid plasticizers and hydrocarbon resins), tackifying resins, methylene acceptors (e.g., phenolic novolac resins), methylene donors (e.g., hexamethylenetetramine (HMT), hexamethoxymethylmelamine (H3M), or combinations thereof), crosslinking systems (e.g., sulfur, sulfur donors, peroxides, bismaleimides, vulcanization accelerators, vulcanization activators, vulcanization retarders (e.g., N-cyclohexylthiophthalimide), anti-reversion agents (e.g., hexamethylenethiosulfate), or combinations thereof), or combinations thereof.
[0020] The rubber composition of the present invention can be produced in a suitable mixer using two successive preparation stages well known to those skilled in the art: a first stage of thermomechanical processing or kneading (called the "non-productive" stage) is carried out at high temperature, up to a maximum temperature between 110°C and 190°C, preferably between 130°C and 180°C, followed by a second stage of mechanical processing (called the "productive" stage) at a lower temperature, typically below 110°C, for example between 40°C and 100°C, which ends with the incorporation of the crosslinking or vulcanization system. A process that can be used to prepare such a composition preferably comprises, for example, the following steps: - during a first stage ("non-productive" stage), mixing in a mixer the reinforcing filler, the fatty acid, the cobalt acetylacetonate into the elastomeric matrix and kneading the whole thermomechanically (for example in one or more steps) until a maximum temperature of between 110°C and 190°C is reached; - cooling the combined mixture to a temperature below 100°C; - then, during the second stage (referred to as the "production" stage), mixing in the sulfur, vulcanization accelerators, vulcanization retarders and methylene donors of the crosslinking system; - Mix the whole to a maximum temperature of less than 110°C.
[0021] By way of example, the first ("non-productive") stage is carried out in a single thermomechanical stage during which all the essential ingredients are introduced into a suitable mixer, such as a standard internal mixer, and then in a second step, after mixing for, for example, 1-2 minutes, other additives, any additional filler coatings or processing aids are introduced, except for the sulfur, vulcanization accelerators and vulcanization retarders of the crosslinking system, and the methylene donor. The total mixing time in this non-productive stage is preferably between 1 and 15 minutes. After cooling the mixture thus obtained, the sulphur, vulcanisation accelerators and retarders of the crosslinking system, as well as the methylene donor, can then be mixed in at low temperature (for example between 40°C and 100°C), typically with an external mixer such as an open mill, and the combined mixture is then mixed for a few minutes (for example between 2 and 15 minutes) (second (production) stage). The crosslinking system can be based preferably on sulfur and a primary vulcanization accelerator, in particular of the sulfenamide type, into which various known secondary accelerators or vulcanization activators, such as zinc oxide, stearic acid as saturated fatty acid, guanidine derivatives (in particular diphenylguanidine), etc., are mixed during a first non-productive phase, during the productive phase, or during both phases.
[0022] According to a preferred embodiment of the invention, the rubber composition is based on a sulfur-based crosslinking system, the sulfur content being preferably greater than 1 phr, more preferably between 2.0 and 10 phr, even more preferably between 3.0 and 8.0 phr, in particular between 4.0 and 6.0 phr. As vulcanization accelerator (primary or secondary), any compound capable of functioning as a vulcanization accelerator of elastomer matrices, such as diene elastomers, in the presence of sulfur may be used, in particular thiazole type accelerators and their derivatives, thiuram type accelerators, or zinc dithiocarbamate, more preferably selected from the group consisting of 2-mercaptobenzothiazyl disulfide (abbreviated as "MBTS"), N-cyclohexyl-2-benzothiazole sulfenamide (abbreviated as "CBS"), N,N-dicyclohexyl-2-benzothiazole sulfenamide ("DCBS"), N-tert-butyl-2-benzothiazole sulfenamide ("TBBS"), N-tert-butyl-2-benzothiazole sulfenimide ("TBSI"), zinc dibenzyldithiocarbamate ("ZBEC"), tetrabenzylthiuram disulfide ("TBZTD"), and combinations thereof.
[0023] According to a preferred embodiment of the invention, the rubber composition is based on a crosslinking system based on at least one vulcanization accelerator, the content of which is preferably greater than 0.2 phr, more preferably between 0.3 and 3.0 phr, even more preferably between 0.4 and 2.0 phr, in particular between 0.5 and 1.0 phr. According to a preferred embodiment of the present invention, the rubber composition is based on a crosslinking system based on at least one anti-reversion agent, preferably the anti-reversion agent is hexamethylene-1,6-bisthiosulfate, more preferably the hexamethylene-1,6-bisthiosulfate is at least one of sodium hexamethylene-1,6-bisthiosulfate, potassium hexamethylene-1,6-bisthiosulfate, calcium hexamethylene-1,6-bisthiosulfate, and combinations thereof. According to a more preferred embodiment of said preferred embodiment, the content of anti-reversion agent is between 0.1 and 5.0 phr, preferably between 0.5 and 4.0 phr, more particularly between 1.0 and 3.0 phr.
[0024] The final composition thus obtained can then be calendered, for example into sheets or plaques, in particular for laboratory characterization, or extruded into the shape of rubber profiled elements which can be used directly as rubber articles. Vulcanization (or curing) can be carried out in known manner, typically at temperatures between 110°C and 190°C, for a sufficient time, e.g., between 5 and 90 minutes, which can vary depending, inter alia, on the cure temperature, the vulcanization system selected, and the vulcanization system kinetics of the composition under consideration. A fourteenth aspect of the present invention is a rubber composite comprising at least one metal monofilament coated with the rubber composition according to any one of the first to thirteenth aspects, preferably the metal monofilament being a steel monofilament. According to a preferred embodiment of the present invention, an article comprises the rubber composition according to any one of the first to thirteenth aspects, and preferably the article comprises the rubber composite according to the fourteenth aspect. According to a more preferred embodiment of the above preferred embodiment, the article is a tire, a leather, a conveyor or a caterpillar track.
[0025] A fifteenth aspect of the present invention is a tire comprising the rubber composition according to any one of the first to thirteenth aspects, and is preferably a tire comprising the rubber composite according to the fourteenth aspect. The tyre of the invention is intended in particular to be fitted to passenger cars, including 4x4 (four-wheel drive) and SUV (sports utility vehicle) vehicles, and industrial vehicles, in particular vans and large vehicles (i.e. buses or large road vehicles (trucks, tractors, trailers)). According to a preferred embodiment of the fifteenth aspect, the rubber composition is an internal rubber composition, which is intended in this specification to mean all the rubber parts of the tire that are not open to the outside of the tire, in other words, not in contact with the ambient air or with the inflation gases and therefore located actually inside the tire structure. Examples include rubber compositions present in particular in the bead zone, in the carcass reinforcement or in the crown reinforcement or belt of the tire. The present invention relates to rubber compositions in the raw state (i.e., before curing) and in the cured state (i.e., after crosslinking or vulcanization). The present invention is further illustrated by the following non-limiting examples. EXAMPLES
[0026] To verify the effect of the present invention, three rubber compositions (C-1 to C-3) were used. The rubber compositions are based on a diene elastomer (NR, as elastomer matrix) reinforced with carbon black (as reinforcing filler), a cobalt salt (cobalt tallate or cobalt acetylacetonate) and a fatty acid (stearic acid, or stearic acid and tall oil type fatty acid). The formulation of the rubber compositions is presented in Table 1, with the contents of the various components given in phr. Each rubber composition was prepared as follows: the reinforcing filler, the cobalt salt, the fatty acid and the various other ingredients (except for the sulfur of the crosslinking system, the vulcanized vulcanization accelerator and the vulcanization retarder (N-cyclohexylthiophthalimide, abbreviated as "CTP") and the methylene donor) were continuously introduced into an internal mixer having an initial vessel temperature of about 60°C, until the mixer was filled to about 70% (volume %). The thermomechanical operation (non-productive phase) was then continued in one step for a total of about 3-4 minutes until a maximum "dropping" temperature of 165°C was reached. The mixture thus obtained was collected and cooled, and then the sulfur of the crosslinking system, the vulcanized vulcanization accelerator and the vulcanization retarder (N-cyclohexylthiophthalimide, abbreviated as "CTP") and the methylene donor were mixed in with an external mixer (homofinisher) at 20-30°C, and the whole was mixed for an appropriate time (for example between 5 and 12 minutes) (productive phase).
[0027] The rubber compositions thus obtained are then calendered either in the form of rubber sheets (2-3 mm thick) or in the form of thin sheets, or in the form of contoured elements which can be used directly (for example as semi-finished tyres) after cutting to the desired dimensions, assembly or both, in order to measure the physical or mechanical properties of the rubber compositions. The tack of each rubber composition in the uncured state was measured at room temperature using a rolling ball tack test device in accordance with ASTM D3121-06 immediately after cutting (for initial tack) and 5 days after cutting (for tack after aging). Using an MTS 381-type cyclic fatigue machine ("Elastomer Test System"), the crack propagation rate, which indicates the crack resistance, was measured for test pieces of the rubber compositions (C-1 to C-3). Test specimens were prepared by curing the rubber compositions in a bell press at 150°C for 25 minutes or at 160°C for 90 minutes, cooling at ambient temperature for one day, and placing in an oven in air at a temperature of 77°C and a relative humidity of 60% for 20 days.
[0028] The crack resistance was measured by repeated tensile movements on specimens that were first accommodated (after the first tensile cycle) and then notched. The tensile specimens consisted of parallelepiped-shaped rubber plaques, e.g., between 1 and 2 mm thick, between 130 and 170 mm long, and between 10 and 15 mm wide, each of whose two lateral ends was covered in the longitudinal direction with a cylindrical rubber bead (diameter 5 mm) so that the specimen could be fixed in the jaws of a tensile tester. The tests were carried out in air at a temperature of 90°C. After accommodation and before the start of the test, three very thin notches between 15 and 20 mm long were made with a razor blade, aligned in the middle of the specimen's width, in the longitudinal direction, one at each end and one in the center. For each tensile cycle, the energy rebound level (amount of energy released during crack propagation) was measured at 1000 J / m 2 The strain rate of the specimen was automatically adjusted to keep it constant at a value equal to . The crack propagation rate, i.e., the crack propagation velocity, was obtained by dividing the length of the crack propagated by the strain by the number of cycles of strain.
[0029] The adhesion and crack resistance results are shown in Table 2 in relative units, with the Reference Example (C-1) being taken as the standard of 100 (it should be remembered that values above 100 represent improved performance). The results in Table 2 show that the Example (C-3) of the present invention has a better adhesion value after aging than the Reference Example (C-1) and the Comparative Example (C-2), and that the Example (C-3) has initial adhesion and crack resistance values equal to or greater than those of the Reference Example (C-1) and the Comparative Example (C-2). In conclusion, the rubber composition can unexpectedly improve tack after aging while maintaining or improving initial tack and crack resistance.
[0030] [Table 1]
[0031] (1) NR: natural rubber (deflocculated); (2) carbon black (ASTM grade N326 (name conforming to ASTM D-1765) manufactured by Cabot); (3) Cobalt tallate ("Dicnate tallate" manufactured by DIC Plastics Corporation); (4) Cobalt(II) acetylacetonate (Aldrich); (5) Stearic acid ("Pristerene 4931" from Uniqema); (6) tall oil type fatty acids (Green Oleo's "GREENFAC 8959 BULK", iodine value: 130-145 (g / 100g)) and stearic acid (Uniqema's "Pristelene 4931"); mass ratio [(tall oil type fatty acids) / (stearic acid)]: 4 / 1; mass ratio of tall oil type fatty acids: C16 fatty acids (palmitic acid): 1.0-6.0%, C18 fatty acids (stearic acid): 0.0-3.0%, C18:1 fatty acids (oleic acid): 30.0-40.0%, C18:2 fatty acids (linoleic acid): 52.0-60.0%, C18:3 fatty acids (α-linolenic acid): 0.0-4.0%; (7) N-(1,3-dimethylbutyl)-N-phenyl-para-phenylenediamine ("Santoflex 6-PPD" from Flexsys); (8) Zinc oxide (industrial grade, Umicore company); (9) Sodium hexamethylene thiosulfate ("Duralink HTS" manufactured by Flexis); (10) Resorcinol (Sumitomo); (11) Hexamethylenetetramine (Degussa); (12) N-(t-butyl)-2-benzothiazolesulfenamide ("Santocure TBBS" from Flexis); (13) N-Cyclohexylthiophthalimide ("Vulkalent G" from Lanxess)
[0032]
Table 2
Claims
1. A rubber composition comprising: an elastomer matrix, - a reinforcing filler, - cobalt acetylacetonate, - fatty acids based on more than 10% by weight of unsaturated fatty acids per 100% by weight of fatty acids; Based on The rubber composition does not contain basic magnesium sulfate inorganic fibers.
2. 10. The rubber composition of claim 1, wherein the elastomeric matrix comprises at least one diene elastomer selected from the group consisting of polyisoprene, polybutadiene, butadiene copolymers, isoprene copolymers, and combinations thereof.
3. 3. The rubber composition of claim 1, wherein the fatty acid content is between 0.1 and 2.0 phr.
4. The rubber composition according to any one of claims 1 to 3, wherein the content of the unsaturated fatty acid per 100% by mass of the fatty acid is more than 50% by mass.
5. 5. The rubber composition according to claim 1, wherein the unsaturated fatty acid is a straight-chain unsaturated fatty acid having 4 to 30 carbon atoms.
6. 6. The rubber composition according to claim 1, wherein the unsaturated fatty acid has 1 to 6 carbon-carbon double bonds.
7. The rubber composition according to any one of claims 1 to 6, wherein the unsaturated fatty acids are based on more than 10% by mass of polyunsaturated fatty acids per 100% by mass of unsaturated fatty acids.
8. The rubber composition according to any one of claims 1 to 7, wherein the unsaturated fatty acid is based on at least one selected from the group consisting of oleic acid, linoleic acid, α-linolenic acid, and combinations thereof.
9. A rubber composite comprising at least one metal monofilament coated with the rubber composition of any one of claims 1 to 8.
10. A tire comprising the rubber composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Tire
JP1993065370A
Rubber composition for adhesion
JP2005325302A
Pneumatic tire
JP2013159169A
Rubber composition and production method thereof
JP2015189797A
Rubber composition for tire, and pneumatic tire
JP2016113589A